1874 Pa. laws 91, Ferries and Bridge Companies, § 31, cl. 5 - (:unkn) unknown (General Publisher, 1874)
If any person . . . shall discharge any pistol, or gun, or any fire-arms on or near said bridges, he, she or they so offending shall forfeit and pay to the said company the sum of five dollars each. . .
--
Keywords: DISCHARGE